Calculating home advantage in the first decade of the 21th century UEFA soccer leagues - Saavedra Garcia, M.; Gutierrez Aguilar, O.; Sa Marques, P.; Torres Tobio, G.; Fernandez Romero, J. J. (Journal of Human Kinetics, 2013)
Home advantage has been studied in different sports, establishing its existence and its possible causes. This article analyzes the home advantage in soccer leagues of UEFA countries in the first part of the 21st century. The sample of 52 countries monitored during a period of 10 years allows us to study 520 leagues and 111,030 matches of the highest level in each country associated with UEFA. Home advantage exists and is significant in 32 of the 52 UEFA countries, where it equals 55.6%. A decrease can be observed in the tendency towards home advantage between the years 2000 and 2010. Values between 55 and 56 were observed for home advantage in the top ten leagues in Europe. It has also been observed that home advantage depends on the level of the league evaluated using UEFA`s 2010/11 Country coefficients. The home advantage is calculated taking into account the teams` position and the points obtained in each of the leagues. A direct relationship was observed with the number of points gained and an inverse relationship was observed with the team position.